1985
DOI: 10.1016/0014-5793(85)81002-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca2+ and a phorbol ester on insulin secretion from islets of langerhans permeabilised by high‐voltage discharge

Abstract: Isolated rat islets of Langerhans permeabilised by high-voltage discharge secreted insulin in response to elevations in Ca2+ over the range 100 nM to 10 ,uM Ca 2+. The phorbol ester, 12-O-tetradecanoylphorbol 13-acetate (TPA), had no effects on insulin secretion in the absence of Ca2+. In the presence of Ca2+ concentrations of > 10 nM, TPA produced dose-related shifts in the Ca 2+-activation curve to lower Ca2+ concentrations, together with marked increases in the maximum secretory response to Caz+. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 25 publications
8
61
1
Order By: Relevance
“…Under physiological conditions, glucose increases [Ca 2+ ] i in ␤-cells, and all maneuvers interfering with this rise impair the stimulation of insulin secretion. Direct evidence that cytoplasmic Ca 2+ triggers exocytosis of insulin granules has been provided by experiments using permeabilized islet cells (11,12) or capacitance recordings in single ␤-cells (13,14). Although progressive desensitization to Ca 2+ occurs in these preparations (7,15), probably because of the loss of essential cytoplasmic constituents, imposed oscillations of [Ca 2+ ] i are able to entrain oscillations of secretion in permeabilized cells, indicating that Ca 2+ has a minute-to-minute triggering role (7).…”
Section: +mentioning
confidence: 99%
“…Under physiological conditions, glucose increases [Ca 2+ ] i in ␤-cells, and all maneuvers interfering with this rise impair the stimulation of insulin secretion. Direct evidence that cytoplasmic Ca 2+ triggers exocytosis of insulin granules has been provided by experiments using permeabilized islet cells (11,12) or capacitance recordings in single ␤-cells (13,14). Although progressive desensitization to Ca 2+ occurs in these preparations (7,15), probably because of the loss of essential cytoplasmic constituents, imposed oscillations of [Ca 2+ ] i are able to entrain oscillations of secretion in permeabilized cells, indicating that Ca 2+ has a minute-to-minute triggering role (7).…”
Section: +mentioning
confidence: 99%
“…Rapid changes in DAG formation have been detected in rat islets following stimulation with glucose or carbachol (Peter-Riesch et al, 1988;Wolf et al, 1989). Although DAG analogues and phorbol esters have been found to stimulate insulin secretion (Virji et al, 1978;Malaisse et al, 1980;Jones et al, 1985) by sensitizing the secretory machinery to Ca 2+ (Jones et al, 1985;Tamagawa et al, 1985), it is debated whether PKC is involved in nutrient-induced insulin secretion (Metz, 1988;Jones and Persaud, 1998). The use of PKC inhibitors has resulted in conflicting conclusions (Jones and Persaud, 1998).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 99%
“…Extrapolation topossible effects of the phorbol ester on cytosolic Ca2+ of normal fl-cells stimulated by tolbutamide would thus be speculative. Experiments using permeabilized islet cells have shown that TPA increases insulin release at a fixed, sub-micromolar, concentration of Ca2+ [38,43] and that this increase is attenuated by polymyxin B, a protein kinase C inhibitor [44]. Taken together, these results and our reports on the interaction of TPA with glucose [10] and tolbutamide (the present study) suggest that the potentiation of insulin release by the phorbol ester results from intracellular events, or non-electrogenic membrane events, that sensitize the releasing machinery to the action of Ca2+.…”
Section: Effects Of Forskolinmentioning
confidence: 99%